Isomerization catalyst, synthesis method and application thereof

By directly synthesizing the molding catalyst, the problems of complex processes, safety hazards and environmental pollution in the prior art are solved, and the preparation of high-content molecular sieve catalysts is realized, which improves catalytic activity and reduces waste liquid emissions.

CN119897157AActive Publication Date: 2025-04-29AOS CATALYSTS (DALIAN) CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510046754.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-29
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

The existing isomerization catalyst preparation process is complex, with safety hazards and environmental pollution problems. At the same time, the content of molecular sieves is low, which affects the catalytic performance.

Method used

The gel is prepared by mixing an aluminum source, alkali source, template agent, silicon source, metal source, ionic liquid and deionized water in the material forming system, and is processed into a molded gel with the desired shape, and finally crystallized in the reactor to obtain the molded Pt/ZSM-48 catalyst.

Benefits of technology

The catalyst preparation process is simplified, the molecular sieve content in the molded body is improved, the catalytic activity is enhanced, and the waste liquid emission is reduced, which is environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119897157A_ABST
    Figure CN119897157A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and discloses an isomerization catalyst as well as a synthesis method and application thereof. The catalyst comprises the following components: 92-99.99 wt% of a * MRE molecular sieve and 0.01-8 wt% of an active metal component, the method is applied to the processing process of petroleum fractions and Fischer-Tropsch synthesis products. The molded catalyst is prepared in one step, and the preparation process of the catalyst is simplified. The formed body is completely composed of the active metal component and the molecular sieve, so that the amount of active sites of the catalyst in unit volume is increased, and the catalytic activity can be improved. According to the method, the formed catalyst is directly obtained, filtering and washing steps in a conventional catalyst production process are avoided, the waste liquid discharge amount is low, and the method is environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to an isomerization catalyst, a synthesis method and application thereof. Background Art

[0002] In recent years, with the continuous growth of the global economy, the market has higher and higher requirements for the quality of gasoline, diesel and lubricating oil. In order to improve the quality of oil products, the normal alkanes must be removed as much as possible. For gasoline, the octane number is an important quantitative indicator to measure its quality. Gasoline with a high octane number has a higher combustion efficiency than gasoline with a low octane number, and the octane number of isoparaffins with the same carbon number is generally greater than the octane number of normal alkanes. Therefore, isomerizing normal alkanes into isoparaffins can increase the octane number of gasoline; for diesel, low-temperature flow performance is one of the main criteria for measuring its quality. If normal alkanes can be selectively isomerized into isoparaffins, its pour point or cold filter point can be reduced, thereby improving its low-temperature performance. As far as lubricating oil is concerned, its quality is closely related to the performance of base oil, because the content of base oil in lubricating oil is usually 70%~99%; the long-chain normal alkanes (also called wax) in the base oil have high pour point and freezing point, poor low-temperature fluidity, and cannot meet the needs of current engines; to obtain lubricating oil with good low-temperature fluidity, the wax in the base oil must be removed.

[0003] At present, the main industrial processes for removing normal alkanes from oil products are solvent dewaxing, catalytic dewaxing and isomerization dewaxing. Compared with the first two processes, the isomerization dewaxing process is to make the wax molecules undergo isomerization reaction, thereby converting the wax into ideal components. This process has the advantages of high product yield and good quality.

[0004] Selective isomerization of normal alkanes into short-chain isoalkanes with fewer side chains can effectively improve the low-temperature fluidity of diesel and lubricating oils. Catalysts with ZSM-48 molecular sieve as carriers have shown excellent performance in the hydroisomerization reaction of long-chain normal alkanes and have attracted much attention in recent years.

[0005] ZSM-48 molecular sieve is a type of molecular sieve with a one-dimensional ten-membered ring straight-through channel skeleton structure of *MRE type disordered structure, and its ideal pore diameter is 0.53 nm*0.56 nm. Catalysts based on ZSM-48 molecular sieves show excellent catalytic performance in the hydroisomerization reaction of long-chain normal alkanes. In recent years, with the rapid development of the national economy, the market demand for ZSM-48 molecular sieves has gradually increased. When ZSM-48 molecular sieves are used as catalysts in actual industrial applications, they often need to be made into finished particles of specific shapes and sizes. The finished product preparation process includes the synthesis of molecular sieve powders and the processing and molding of catalyst particles.

[0006] In general, a complete isomerization catalyst requires two parts: the synthesis of molecular sieves and the loading of active metal components. The synthesis of ZSM-48 molecular sieve powder is industrially carried out by hydrothermal synthesis. This method uses water as a solvent, and the materials are mixed in a certain ratio to obtain a sol. The sol is crystallized between 80 and 200 ° C and under the autogenous pressure of water. After the crystallization is completed, the product is filtered, washed and dried to obtain a molecular sieve powder. The loading of active metal components requires the molecular sieve to be formed first. Specifically, the molecular sieve powder needs to be mixed with additives such as a binder, a plasticizer, an extrusion aid, and a pore-forming agent to obtain a plastic body, and then the finished product is obtained by kneading, curing, drying and roasting; then a certain amount of active metal component solution is mixed with molecular sieve particles and impregnated to finally obtain an active metal component / molecular sieve catalyst. Patent documents such as US5882505, CN1792451, 1788844, and 101245260 all describe in detail the preparation method of alkane isomerization catalysts using molecular sieves as carriers.

[0007] The above method first prepares the molecular sieve powder, then shapes, calcines and dries it, and then impregnates the loaded metal active components to obtain the finished catalyst. The process is long and complicated. In addition, the hydrothermal crystallization process of the molecular sieve is carried out under high pressure, which poses a safety hazard; the filtering and washing process of the powder produces a large amount of wastewater, causing environmental pollution; the catalyst molding requires the addition of additives such as binders. Due to the introduction of additives, the content of molecular sieve in the finished molecular sieve catalyst is generally 60~80%, and cannot reach 100%, which affects the performance of the molecular sieve.

[0008] In order to solve the above problems, people have done a lot of research on simplifying the molecular sieve molding process and increasing the content of molecular sieve in the molded body.

[0009] The researchers used raw materials with a certain shape to directly produce molecular sieves with the same shape as the raw materials without the need for reshaping, which can simplify the molecular sieve catalyst preparation process.

[0010] For example, Sachse et al. prepared a shaped ZSM-5 catalyst using SiO2 monolithic material as raw material. The method placed the SiO2 monolithic material in a solution with a molar ratio of SiO2:NaOH:NaAlO2:TPAOH:H2O =1:0.15:0.09:0.004:33, and crystallized it at 150 °C for 24 hours to obtain a shaped catalyst (Micropor. Mesopor. Mater., 2011, 140(1-3): 58-68). The method used SiO2 monolithic material as the silicon source for molecular sieve synthesis, and the crystallization process remained in the solid phase, but other raw materials such as aluminum source NaAlO2 still existed in the aqueous solution, and the crystallization was still a hydrothermal process. Although the finished molecular sieve maintained the shape of the monolithic material, the reaction process was limited by mass transfer due to the separation of the reaction raw materials in the solid and liquid phases, and the crystallization could not be complete. The content of ZSM-5 in the finished product was only 38%.

[0011] In order to increase the content of molecular sieve in the finished molecular sieve catalyst, researchers have done a lot of work to crystallize the binder and other additives added in the molding process into molecular sieves. For example, patent CN106745057A discloses a method for preparing an AEI / MFI eutectic molecular sieve catalyst. The method mixes MFI type silica-alumina molecular sieve, FAU type silica-alumina molecular sieve and silica sol, and converts them into an integrated AEI / MFI eutectic molecular sieve catalyst through hydrothermal treatment in an aqueous solution containing organic amine, and then calcines to obtain the finished catalyst.

[0012] The above method crystallizes part of the raw materials in the form of integral materials under hydrothermal conditions, and obtains an integral catalyst in one step, which simplifies the preparation process. However, other raw materials still exist in the aqueous solution, and crystallization is still a hydrothermal process, which poses a safety hazard; the reaction raw materials are divided into solid and liquid phases, the reaction process is limited by mass transfer, and the finished product contains unconverted raw materials, and the molecular sieve content is not high. Moreover, although a molded body composed entirely of molecular sieves can be obtained, it is still necessary to synthesize the original molecular sieve powder; the molding process adds a crystallization step, which increases the manufacturing cost. In addition, these methods use integral material shape raw materials, which are limited by the raw material material and have a single shape. At present, the actual finished product shapes of the molded catalyst are rich, including spherical, strip, cylindrical, honeycomb, four-leaf clover, three-leaf clover, external gear, non-porous external gear, plum blossom, porous plum blossom, seven-hole sphere, non-porous sphere, seven-rib wheel, four-hole, four-leaf butterfly, etc.

[0013] The above work is all conducted on shaped molecular sieves. There is still much to be studied about shaped catalysts, especially shaped catalysts combining metal active components and molecular sieves in one step. There is no similar work at present. Summary of the invention

[0014] In order to overcome the deficiencies of the prior art, the present invention provides an isomerization catalyst, a synthesis method and its application, which can simultaneously achieve the goals of simplifying the isomerization catalyst preparation process and increasing the molecular sieve content in the molded catalyst. The catalyst based on ZSM-48 molecular sieve exhibits excellent catalytic performance in the hydroisomerization reaction of long-chain normal alkanes. The present invention particularly provides a method for directly synthesizing a molded catalyst with respect to active metal components and ZSM-48 molecular sieves.

[0015] The above object of the present invention is achieved by the following technical scheme: A method for synthesizing an isomerization catalyst, comprising the steps of: 1. Mixing an aluminum source, an alkali source, a template, a silicon source, a metal source, an ionic liquid and deionized water to prepare a gel; 2. The gel prepared in step 1 is fed into a material forming system to be processed into a shaped gel having a desired shape; 3. The molded gel obtained in step 2 is placed into a reactor for crystallization to obtain a molded Pt / ZSM-48 molded catalyst.

[0016] Furthermore, the metal source in step 1 refers to one or more metal acids, metal salts, chlorides, amine complexes, carbonyl complexes of Group VIII among Pt, Pd, and Ir, or a mixture of two or more thereof. The Group VIII noble metal is composed of one or more of Pt, Pd, and Ir.

[0017] In a further preferred embodiment of the present invention, the metal source in step 1 is Pt and Pd.

[0018] Furthermore, the template agent described in step 1 is one or more of hexamethylammonium bromide, hexamethylammonium hydroxide, and 1,6-hexanediamine.

[0019] Furthermore, the ionic liquid described in step 1 is Br - ,I - , Cl - 、BF4 - 、NO3 - 、CH3COO - One or more of the following; the cation is an alkyl-substituted imidazolium ion [Rim] + , alkyl-substituted pyridinium ion [Rpy] + , alkyl quaternary ammonium salt ion [NR4] + One or more of the following, R is a C1-C16 alkyl group.

[0020] Furthermore, the aluminum source in step 1 is one or both of sodium aluminate and pseudo-boehmite; the silicon source is silica sol; and the alkali source is one or both of sodium hydroxide and potassium hydroxide.

[0021] Furthermore, the molar ratio of the aluminum source, alkali source, template, silicon source, metal source, ionic liquid and deionized water in step 1 is (0.005-0.009): (0.01-1): (0.1-0.25): 1: (0.008-0.1): (0.2-1): (10-45).

[0022] Furthermore, the material forming system in step 2 is specifically as follows: a conveyor belt, a cavity, and a receiving hopper are connected in sequence, the conveyor belt is controlled by a motor with an operation panel, a box shell is provided outside the cavity, an ultrasonic oscillator is provided at the bottom of the box shell, and a bracket is also provided at the bottom of the box shell.

[0023] Furthermore, the step 2 is specifically as follows: placing the gel on a molding mold and then placing it on a conveyor belt, turning on a motor to convey it to the inside of the cavity, and using an ultrasonic oscillator at the bottom to oscillate the gel until it is uniformly formed, and the formed gel is sent to a receiving hopper.

[0024] Furthermore, the crystallization conditions in step 3 are: crystallization at 170-190° C. for 5-24 hours.

[0025] Another object of the present invention is to protect an isomerization catalyst, which comprises 92-99.99 wt % of *MRE molecular sieve and 0.01%-8% of active metal component, and is synthesized by the above-mentioned isomerization catalyst synthesis method.

[0026] Another object of the present invention is to claim the application of the above isomerization catalyst, specifically in the processing of petroleum fractions and Fischer-Tropsch synthesis products.

[0027] Furthermore, the isomerization catalyst is used for isomerization pour point depressing and isomerization dewaxing.

[0028] The crystallization process of the present invention is carried out by placing the formed gel in a container, in which a certain amount of water may be placed in advance, but it is not necessary for the water to be in direct contact with the formed gel. The heating method used in the crystallization process is, for example, oil bath heating, oven heating and microwave heating.

[0029] After the crystallization is completed, the molded product prepared by the present invention does not need to be filtered or washed, and maintains the same shape and size as the molded gel. The product is completely composed of active metal components and molecular sieves, and the molecular sieve skeleton structure is the ZSM-48 molecular sieve confirmed by the International Zeolite Association.

[0030] To facilitate understanding of the present invention, the term "direct forming" is defined below. The defined terms have the meanings commonly understood by those of ordinary skill in the art to which the present invention relates.

[0031] Unless otherwise specified, "direct molding" in this article refers to the process or step of pre-processing the gel used for synthesizing molecular sieves into a molded gel with a certain shape, size and mechanical strength by compression, extrusion, rotation, spraying, etc., and then directly obtaining a molded molecular sieve with the same shape as the molded gel by heating.

[0032] Compared with the prior art, the present invention has the following beneficial effects: the present invention obtains a shaped catalyst in one step, thus simplifying the catalyst preparation process. The shaped body is completely composed of active metal components and molecular sieves, thus increasing the amount of active sites per unit volume of the catalyst and improving its catalytic activity. The method directly obtains a shaped catalyst, thus avoiding the filtering and washing steps in the conventional catalyst production process, resulting in low waste liquid discharge and being environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments: Figure 1 It is a schematic diagram of the structure of the material forming system of the present invention; Figure 2 is the XRD spectrum of the sample in Example 1 of the present invention; Figure 3 is the HAADF diagram of the sample in Example 1 of the present invention; Figure 4 This is a physical picture of the formed gel in Example 1 of the present invention; Figure 5 This is a physical picture of the molded Pt / ZSM-48 catalyst in Example 1 of the present invention.

[0034] In the figure, 1. conveyor belt; 2. motor; 3. operation panel; 4. ultrasonic oscillator; 5. bracket; 6. box shell; 7. hopper; 8. cavity. DETAILED DESCRIPTION

[0035] The present invention is described in detail below by specific examples, but the protection scope of the present invention is not limited. Unless otherwise specified, the experimental methods used in the present invention are all conventional methods, and the experimental equipment, materials, reagents, etc. used can be obtained from commercial channels.

[0036] Example 1

[0037] 0.05g pseudo-boehmite (78.6wt% Al2O3) was placed in a 100ml beaker, 50.75g deionized water was added, and the mixture was stirred at room temperature for 30 minutes. 0.03g potassium hydroxide was added, and after stirring at room temperature for 30 minutes, 5.4g hexamethylammonium bromide was added for 30 minutes. 15g silica sol with a concentration of 30wt% was added, and stirring was continued for 30 minutes. 23.4mL H2PtCl6 solution (containing 0.005g Pt per mL) was added, and after stirring for 30 minutes, 2.87g 1-ethyl-3-methylimidazolium bromide ionic liquid was added, and the mixture was stirred until uniform and treated at 90°C, and extruded into cylindrical strips. The shaped cylindrical strip gel was placed in a crystallization reactor with a polytetrafluoroethylene reactor liner and crystallized at 180°C for 18h.

[0038] After the crystallization is completed, the crystallization kettle is cooled to room temperature to obtain a molded catalyst, and the molded catalyst is ground into powder. According to XRD spectrum analysis, the molecular sieve is ZSM-48, such as Figure 1 As shown; the formed catalyst was calcined at 550 ° C in an air atmosphere for 6 h, and then reduced at 400 ° C in a H2 atmosphere (25 ml / min) for 4 h to prepare 0.48 wt% Pt / ZSM-48 for HAADF photography. The Pt particles in the catalyst were evenly distributed, as shown Figure 2 As shown; the shaped gel has the same shape as the shaped Pt / ZSM-48 catalyst, such as Figure 3 shown.

[0039] Example 2

[0040] 0.09g pseudo-boehmite (78.6wt% Al2O3) was placed in a 100ml beaker, 13.5g deionized water was added, and the mixture was stirred at room temperature for 30 minutes. 3g potassium hydroxide was added, and after stirring at room temperature for 30 minutes, 3.15g hexamethyldiamine hydroxide was added for 30 minutes. 15g silica sol with a concentration of 30wt% was added, and stirring was continued for 30 minutes. 292.5mL H2PtCl6 solution (containing 0.005g Pt per mL) was added, and after stirring for 30 minutes, 14.3g 1-ethyl-3-methylimidazolium bromide ionic liquid was added, and the mixture was stirred until uniform and treated at 90°C, and extruded into cylindrical strips. The shaped cylindrical strip gel was loaded into a crystallization reactor with a polytetrafluoroethylene reactor liner and crystallized at 170°C for 24h.

[0041] After the crystallization is completed, the crystallization kettle is cooled to room temperature to obtain a molded catalyst, and the molded catalyst is ground into powder. XRD spectrum analysis shows that the molecular sieve is ZSM-48; the molded catalyst is placed in an air atmosphere and calcined at 550 °C for 6 h to remove the template, and then reduced at 400 °C in a H2 atmosphere (25 ml / min) for 4 h to prepare a 5 wt% Pt / ZSM-48 catalyst.

[0042] Example 3

[0043] 0.07g of sodium aluminate was placed in a 100ml beaker, 60.75g of deionized water was added, and the mixture was stirred at room temperature for 30 minutes. 2.1g of potassium hydroxide was added, and after stirring at room temperature for 30 minutes, 5.4g of hexamethylammonium bromide and 0.45g of 1,6-hexanediamine were added for 30 minutes. 15g of 30wt% silica sol was added, and stirring was continued for 30 minutes. 29.2mL of H2PtCl6 solution (containing 0.005g of Pt per mL) was added, and after stirring for 30 minutes, 7.16g of 1-ethyl-3-methylimidazolium bromide ionic liquid was added, and the mixture was stirred until uniform and treated at 90°C, and extruded into clover strips. The formed cylindrical strip gel was loaded into a crystallization reactor with a polytetrafluoroethylene reactor liner and crystallized at 190°C for 5h.

[0044] After the crystallization is completed, the crystallization kettle is cooled to room temperature to obtain a molded catalyst, and the molded catalyst is ground into powder. XRD spectrum analysis shows that the molecular sieve is ZSM-48; the molded catalyst is placed in an air atmosphere and calcined at 550 °C for 6 h to remove the template, and then reduced at 400 °C in a H2 atmosphere (25 ml / min) for 4 h to prepare a 0.5 wt% Pt / ZSM-48 catalyst.

[0045] Example 4

[0046] 0.09g of pseudo-boehmite was placed in a 100ml beaker, 60.75g of deionized water was added, and the mixture was stirred at room temperature for 30 minutes. 0.84g of potassium hydroxide was added, and after stirring at room temperature for 30 minutes, 5.4g of hexamethylammonium bromide and 0.45g of 1,6-hexanediamine were added for 30 minutes. 15g of 30wt% silica sol was added, and stirring was continued for 30 minutes. 146.25mL of H2PtCl6 solution (containing 0.005g of Pt per mL) was added, and after stirring for 30 minutes, 11.5g of 1-ethyl-3-methylimidazolium bromide ionic liquid was added, and the mixture was stirred until uniform and treated at 90°C, and extruded into clover strips. The formed cylindrical strip gel was placed in a crystallization reactor with a polytetrafluoroethylene reactor liner and crystallized at 190°C for 5h.

[0047] After the crystallization is completed, the crystallization kettle is cooled to room temperature to obtain a molded catalyst, and the molded catalyst is ground into powder. XRD spectrum analysis shows that the molecular sieve is ZSM-48; the molded catalyst is placed in an air atmosphere and calcined at 550 °C for 6 h to remove the template, and then reduced at 400 °C in a H2 atmosphere (25 ml / min) for 4 h to prepare a 2.5 wt% Pt / ZSM-48 catalyst.

[0048] Comparative Examples 1-4

[0049] The ZSM-48 molecular sieves of Comparative Examples 1-4 were prepared according to the method described in Patent CN111137905B, and the specific steps were as follows: (1) 1,6-hexanediamine, sodium hydroxide and water were mixed together, and dissolved by electric stirring. Under electric stirring at 25°C, alkaline silica sol was gradually added thereto through a peristaltic pump, and aged at 25°C for 2h. The molar ratio of each substance was Na2O:SiO2:C6H 16 N2:H2O=0.15:6:1:150. (2) Transfer to a pressure vessel with a polytetrafluoroethylene liner, and then crystallize in a homogenizer (dynamic oven, 800 rpm) at 165°C for 10 hours. (3) After cooling to room temperature, open the kettle, add an alkaline aluminum solution containing sodium aluminate and hexamethylammonium bromide (the concentration of the aluminum source is 0.003 mol% in terms of Al2O3) at one time, adjust the pH of the alkaline aluminum solution to 12 with sodium hydroxide, so that SiO2:Al2O3:hexamethylammonium bromide=125:1:0.004, then seal the pressure vessel, and then dynamically crystallize in a homogenizer at 170°C at 800 rpm for 24 hours. (4) After cooling to room temperature, open the kettle, separate, wash and dry the product, and finally obtain ZSM-48 molecular sieve raw powder.

[0050] The ZSM-48 molecular sieve raw powder was calcined at 550°C for 6 hours, and then 2% of the total mass of sesbania powder was added, the amount of sodium carboxymethyl cellulose added was 0.3%, the mass concentration of nitric acid was 8%, the water-powder ratio was 0.85, and the cylindrical ZSM-48 molecular sieve was obtained by extrusion molding, and calcined at 550°C for 5 hours.

[0051] Comparative Example 1

[0052] Take 2 g of the above ZSM-48 molecular sieve, impregnate it with 2.0 mL of H2PtCl6 solution (each mL contains 0.0048 g of Pt), place it at room temperature for 12 hours, dry it at 120°C for 2 hours, and then reduce it at 500°C in a hydrogen atmosphere for 4 hours to obtain a catalyst containing 0.5 wt.% Pt.

[0053] Comparative Example 2

[0054] Take 2 g of the above ZSM-48 molecular sieve, impregnate it with 2.0 mL of H2PtCl6 solution (each mL contains 0.05 g of Pt), place it at room temperature for 12 hours, dry it at 120°C for 2 hours, and then reduce it at 500°C in a hydrogen atmosphere for 4 hours to obtain a catalyst containing 5 wt.% Pt.

[0055] Comparative Example 3

[0056] Take 2 g of the above ZSM-48 molecular sieve, impregnate it with 2.0 mL of H2PtCl6 solution (each mL contains 0.005 g of Pt), place it at room temperature for 12 hours, dry it at 120°C for 2 hours, and then reduce it at 500°C in a hydrogen atmosphere for 4 hours to obtain a catalyst containing 0.5 wt.% Pt.

[0057] Comparative Example 4

[0058] Take 2 g of the above ZSM-48 molecular sieve, impregnate it with 2.0 mL of H2PtCl6 solution (each mL contains 0.025 g of Pt), place it at room temperature for 12 hours, dry it at 120°C for 2 hours, and then reduce it at 500°C in a hydrogen atmosphere for 4 hours to obtain a catalyst containing 2.5 wt.% Pt.

[0059] 1.0 mL of the catalyst in each of Examples 1-4 and Comparative Examples 1-4 was loaded into a stainless steel tube reactor and evaluated by the hydroisomerization reaction of n-dodecane. The reaction conditions were: reaction pressure of 0.1 MPa, liquid space velocity of n-dodecane of 1.0 h -1 The molar ratio of hydrogen to n-dodecane is 15. The reaction products are analyzed by online gas chromatography. The results are listed in Table 1.

[0060] Table 1 Results of the application of catalysts in the hydroisomerization of n-dodecane

[0061] n-dodecane conversion rate (%) = 1-unconverted n-dodecane amount / n-dodecane feed amount × 100% Isomerization selectivity (%) = amount of converted isomerized (branched) dodecane / total amount of all converted normal dodecane × 100% Isomerization yield (%) = isomerization selectivity (%) × n-dodecane conversion rate (%) × 100% It can be seen from Table 1 that the conversion rate of n-dodecane and the selectivity of isoparaffins of the molded catalyst prepared by the present method are improved compared with the catalyst of the comparative example.

[0062] The above-described embodiments are only preferred embodiments of the present invention, but not all feasible embodiments of the present invention. For those skilled in the art, any obvious changes made thereto without departing from the principles and spirit of the present invention should be considered to be included in the scope of protection of the claims of the present invention.

Claims

1. A method for synthesizing an isomerization catalyst, characterized in that the steps include: S1. mixing an aluminum source, an alkali source, a template, a silicon source, a metal source, an ionic liquid and deionized water to prepare a gel; S2. The gel prepared in step S1 is processed into a shaped gel having a desired shape by entering a material forming system; S3. The molded gel obtained in step S2 is placed into a reaction kettle for crystallization to obtain a molded Pt / ZSM-48 molded catalyst.

2. The method for synthesizing an isomerization catalyst according to claim 1, characterized in that: The metal source described in step S1 refers to one or more of Pt, Pd, and Ir, one or a mixture of two or more of metal acids, metal salts, chlorides, amine complexes, and carbonyl complexes of Group VIII; wherein the Group VIII noble metal is composed of one or more of Pt, Pd, and Ir.

3. The method for synthesizing the isomerization catalyst according to claim 1, characterized in that: The template agent described in step S1 is one or more of hexamethylammonium bromide, hexamethylammonium hydroxide, and 1,6-hexanediamine.

4. The method for synthesizing an isomerization catalyst according to claim 1, characterized in that: The ionic liquid described in step S1 is Br - ,I - , Cl - 、BF4 - 、NO3 - 、CH3COO - One or more of the following; the cation is an alkyl-substituted imidazolium ion [Rim] + , alkyl substituted pyridinium ion [Rpy] + 、Alkyl quaternary ammonium salt ion [NR4] + One or more of the following, wherein R is a C1-C16 alkyl group; the aluminum source in step S1 is one or both of sodium aluminate and pseudo-boehmite; the silicon source is silica sol; and the alkali source is one or both of sodium hydroxide and potassium hydroxide.

5. The method for synthesizing an isomerization catalyst according to claim 1, characterized in that: The molar ratio of the aluminum source, alkali source, template, silicon source, metal source, ionic liquid and deionized water in step S1 is (0.005-0.009): (0.01-1): (0.1-0.25): 1: (0.008-0.1): (0.2-1): (10-45).

6. The method for synthesizing an isomerization catalyst according to claim 1, characterized in that: The material forming system in step S2 is specifically as follows: a conveyor belt, a cavity, and a receiving hopper are connected in sequence, the conveyor belt is controlled by a motor switch with an operation panel, a box shell is provided outside the cavity, an ultrasonic oscillator is provided at the bottom of the box shell, and a bracket is also provided at the bottom of the box shell.

7. The method for synthesizing an isomerization catalyst according to claim 1, characterized in that: The step S2 specifically includes: placing the gel on a forming mold and then placing it on a conveyor belt, turning on a motor to convey it to the inside of the cavity, and using an ultrasonic vibrator at the bottom to vibrate the gel until it is uniformly formed, and the formed gel is sent to a receiving hopper.

8. The method for synthesizing an isomerization catalyst according to claim 1, characterized in that: The crystallization conditions in step S3 are: crystallization at 170-190° C. for 5-24 hours.

9. An isomerization catalyst, comprising 92-99.99 wt% of MRE molecular sieve, characterized in that: The isomerization catalyst is synthesized by the method for synthesizing the isomerization catalyst as claimed in claim 1.

10. The use of the isomerization catalyst according to claim 9, characterized in that: It is specifically used in the processing of petroleum fractions and Fischer-Tropsch synthesis products.

Citation Information

Patent Citations

  • Adhesive-free AEI / MFI eutectic silicon-aluminum molecular sieves as well as synthetic method and application

    CN106745057A

  • ZSM-48 molecular sieve and its preparation method

    CN111137905B

  • Conversion of fisher-tropsch waxes to lubricants by countercurrent processing

    US5882505A

  • Method for synthesizing alkane hydroisomerization catalyst support

    CN109422282A

  • ZSM-12 molecular sieve supported high-dispersion Pt catalyst and preparation method thereof

    CN109772443A